PRESOLAR SPINEL GRAINS FROM THE MURRAY AND MURCHISON CARBONACEOUS CHONDRITES - Zinner E.; Amari S.; Guinness R.; Nguyen A.; Stadermann F.J.; Walker R.M.; Lewis R.S. (My University, 2003)
With a new type of ion microprobe, the NanoSIMS, we determined the oxygen isotopic compositions of small (<1μm) oxide grains in chemical separates from two CM2 carbonaceous meteorites, Murray and Murchison. Among 628 grains from Murray separate CF (mean diameter 0.15 μm) we discovered 15 presolar spinel and 3 presolar corundum grains, among 753 grains from Murray separate CG (mean diameter 0.45 μm) 9 presolar spinel grains, and among 473 grains from Murchison separate KIE (mean diameter 0.5 μm) 2 presolar spinel and 4 presolar corundum grains. The abundance of presolar spinel is highest (2.4%) in the smallest size fraction. The total abundance in the whole meteorite is at least 1 ppm, which makes spinel the third-most abundant presolar grain species after nanodiamonds (if indeed a significant fraction of them are presolar) and silicon carbide. The O-isotopic distribution of the spinel grains is very similar to that of presolar corundum, the only statistically significant difference being that there is a larger fraction of corundum grains with large 17O excesses (17O/16O > 1.5 x 10-3), which indicates parent stars with masses between 1.8 and 4.5 M#.